Post-Harvest Handling Techniques Of Liberica Coffee (Coffea Liberica Var.) To Become Coca Coffea Products In Sei Kemangkus Plantation, Rungan District, Gunung Mas Regency, Central Kalimantan - Eriansyah, Satria; Setiawan, Andi; Warsito, Kabul (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
In this case, Coka Coffea producers have determined the right direction in producing Coka Coffea products which are enjoyed by coffee lovers in Central Kalimantan. This research aims to determine the income of Coka Coffea product producers as players in the roast bean coffee business with a distinctive taste and aroma, whose Liberica coffee is grown and harvested from the Sei Kemangkus area, Rungan District, Gunung Mas, Central Kalimantan. Post-harvest handling, often referred to as primary processing, is a term used for all treatment from harvest until the commodity can be consumed